Priorities of mate selection during Covid-19 pandemic compared to the last decade - Rastegari, Peyman; Razeghi, Narges; Zabihi, Mahdi (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to investigate the priorities of couple selection in the corona age and compare it with the last ten years Methods: This study was a comparative causal study and the statistical population included young people aged 22 to 40 years old students of Tehran Azad and State University, of whom 200 were randomly selected (100 females, 100 males) in the age range of 22 to 40 years. Years that were selected by available and targeted sampling. The tools used in the present study consisted of two parts: 1) individual characteristics of the participant, 2) emotional partner selection test (part of priorities and part of importance and standard requirements). The analysis of the information obtained from the questionnaire was performed through spss24 software in two descriptive and inferential sections (binomial test). Results: The results showed that the criteria: adaptation, good health, education, intelligence and intellectual adequacy, sociality, ambition and diligence, good cooking and housekeeping, no previous sexual relations and similar political background rank better (lower average) than before They have also shown a significant difference, and therefore have shown a change in current and past 10 year priorities. Social well-being and fertility have shown a significant change with the past (P=0.01). Conclusion: this change indicates a decrease in the priority of these criteria over the past, and other criteria have not shown a significant difference in prioritization with the past.